2019
DOI: 10.20961/jab.v18i2.330
|View full text |Cite
|
Sign up to set email alerts
|

Why Does the Recently Adopted Performance Measurement System in Indonesian Local Government Not Work?

Abstract: The purpose of this study is to gain insight on the implementation of a newly adopted Performance Measurement System (PMS) in Sabang local government-Indonesia. It is a case study based qualitative research which was carried out at the local government of Sabang. Data were collected through document analysis, questionnaires, and followed by semi-structure interviews. The questionnaires were distributed to key officers of 7 working unit/departments (or Satuan Kerja Perangkat Daerah) out of 31 departments in tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
4

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(20 citation statements)
references
References 16 publications
3
13
4
Order By: Relevance
“…This implies that increase in national government support is likely to decrease the adoption of SPPM at county governments. This finding contradicts many previous studies which found a positive and significant association (Fahlevi et al., 2018; Gowon, Rohman, Basuki, & Fortunasri, 2018; Eliuz et al., 2017; Brusca & Montesinos, 2016).…”
Section: Findings and Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…This implies that increase in national government support is likely to decrease the adoption of SPPM at county governments. This finding contradicts many previous studies which found a positive and significant association (Fahlevi et al., 2018; Gowon, Rohman, Basuki, & Fortunasri, 2018; Eliuz et al., 2017; Brusca & Montesinos, 2016).…”
Section: Findings and Discussioncontrasting
confidence: 99%
“…From this model, compulsory performance measurement requirement from national government and nationwide database on public procurement performance in counties were found to have no relation with adoption of SPPM. These findings uniquely stand out among previous studies (Fahlevi et al. , 2018; Gowon et al.…”
Section: Findings and Discussionsupporting
confidence: 88%
See 3 more Smart Citations